Eastern European Scientists in Mexico: An Exploration of their Immigration Experiences - Isabel Izquierdo (Arizona State University, 2011)
In this work we identified three highly skilled immigration waves during the 20th Century in Mexico: the Spanish, the South Americans, and the Eastern Europeans in particular those from the Former Soviet Union. In the last group, we analyzed the cases of nine scientists migrations experiences that came to Mexico in the nineties. The analysis focused on the causes that the scientists had to leave that region and to remain in Mexico.